PENERAPAN MEDIA PERMAINAN LACAK KARTU BILANGAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI OPERASI HITUNG BILANGAN CACAH - Junaidah; Anis Safira (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2023)
This research aims to find out how the application of the Number Card Tracking Media Game can improve the learning outcomes of 3th grade MIN 22 Pidie students on whole number counting operations. The research design used in this research was classroom action research (CAR) using the Kurt Lewin model. The subjects in this research were 3th grade students at MIN 22 Pidie, totaling 22 students consisting of 19 male and 13 female students. Data collection in research was carried out by observation, tests/evaluations, and field notes. The results of the research showed that the average individual score in cycle I was 69.86 with a completion percentage of 45.45% and in cycle II it was 76.68 with a completion percentage of 72.72% and experienced an increase in cycle III, which are 92.81 with a percentage 100%. It can be concluded that the application of the number card tracking game media can improve student learning outcomes in whole number counting operation material for class III MIN 22 Pidie